A Plasmonic Coupling Substrate Based on Sandwich Structure of Ultrathin Silica‐Coated Silver Nanocubes and Flower‐Like Alumina‐Coated Etched Aluminum for Sensitive Detection of Biomarkers in Urine. Issue 10 (2nd February 2017) - Nguyen, Minh‐Kha; Su, Wei‐Nien; Hwang, Bing‐Joe
Abstract : Interactions between substrate and plasmonic nanostructures can give rise to unique optical properties and influence performance in plasmonic biosensing applications. In this study, a substrate with low refractive index and roughness based on flower‐like alumina‐coated etched aluminum foil (f‐Al2 O3 /e‐Al) has been fabricated. Silver@silica (Ag@SiO2 ) nanocubes (NCs) assemble in an edge–edge configuration when deposited on this substrate. The rough surface texture of f‐Al2 O3 /e‐Al provides a pathway for coupling of incident light to surface plasmons. The Ag@SiO2 /f‐Al2 O3 /e‐Al substrate exhibits a coupling efficiency of laser light sources into surface plasmon hotspots for both surface‐enhanced Raman scattering (SERS) and metal‐enhanced photoluminescence (MEPL). Moreover, the shelf life of this substrate is significantly improved due to a reduction in oxygen diffusion rate mediated by the ultrathin silica spacer and the flower‐like Al2 O3 dielectric layer. Creatinine and flavin adenine dinucleotide are biomolecules present in human blood and urine. With advanced label‐free SERS and MEPL techniques, it is possible to detect these biomarkers in urine, allowing cheap, noninvasive, yet sensitive analysis. The approach explored in this work can be developed into a powerful encoding tool for high‐throughput bioanalysis. Abstract : Ag@SiO2 /f‐Al2 O3 /e‐Al substrate is developed with strong plasmonic coupling of edge–edge orientation within Ag@SiO2 nanocubes. The sandwich structure creates a "multiple light source effect" to enhance efficiency of surface plasmon hotspots and shows a reproducible bifunctionality for detecting creatinine and flavin adenine dinucleotide by surface‐enhanced Raman scattering and metal‐enhanced photoluminescence.